Fibroscan Reliably Rules Out Advanced Liver Fibrosis and Significant Portal Hypertension in Alcoholic Patients. Issue 10 (November 2019) - Salavrakos, Melissa; Piessevaux, Hubert; Komuta, Mina; Lanthier, Nicolas; Stärkel, Peter
Abstract : Background/Goals: To date, there is no consensus on optimal cut-off values and timing of transient elastography (TE, Fibroscan) for fibrosis staging and prediction of portal hypertension in alcoholic liver disease. We evaluated the accuracy of Fibroscan for the diagnosis of fibrosis and clinically significant portal hypertension in alcoholic patients. Study: Heavy drinkers admitted to our standardized alcohol withdrawal program were evaluated by Fibroscan, by transjugular hepatic venous pressure gradient (HVPG) measurement and liver biopsy if significant fibrosis was suspected and by upper gastrointestinal endoscopy. All investigations were performed within 3 days of admission. Patients who had remained abstinent for 2 weeks underwent a second Fibroscan. Results: A total of 118 patients were included. Fibroscan correlated well with histology and HVPG. Negative predictive value of 92% and 93% for ruling out severe fibrosis (≥F3) and cirrhosis, and optimal cut-offs at ≥11.7, ≥15.2, and ≥21.2 kPa for F2, F3, and F4, respectively, were found. In abstinent patients, a mean decrease of 2.7 kPa improved concordance between Fibroscan and histology. A TE value of 30.6 kPa predicted a HVPG>10 mm Hg with 94% specificity and showed a good negative predictive value of 84% for ruling out the presence of varices at endoscopy. Steatosis, alcoholic hepatitis, sinusoidal fibrosis, cholestasis, and high transaminases did not influence TE values. Conclusions: Fibroscan is an accurate non-invasive method for the diagnosis of fibrosis in alcoholic patients. TE values below 11 and 30 kPa likely rule out significant fibrosis and varices, respectively. Abstract : Supplemental Digital Content is available in the text.